2010
DOI: 10.1111/j.1542-4758.2009.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3‐hour daily hemodialysis and paricalcitol in patients with severe secondary hyperparathyroidism: A case series

Abstract: Patients with poor metabolic control receiving conventional hemodialysis are at risk for developing severe secondary hyperparathyroidism. We postulated that daily hemodialysis may be effective at controlling parathyroid hormone (PTH) in the setting of severe secondary hyperparathyroidism by improving the control of hyperphosphatemia and allowing increased use of vitamin D analogs. We present 5 patients with severe secondary hyperparathyroidism (median iPTH=1783 pg/mL) who were treated with 3-hour daily hemodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The previously mentioned studies on Ca‐P‐PTH intradialysis balance were performed in the setting of thrice‐weekly “conventional” dialysis. While the effect of the increase in dialysis frequency and/or duration on uraemic bone disease has been extensively described, nonconventional schedules, such as incremental or short daily dialysis, have been less studied by intradialysis profiles . Furthermore, the new generation of portable dialysis machines, with low‐flow dialysate, presents a different mass transfer profile, which has not yet been completely clarified …”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned studies on Ca‐P‐PTH intradialysis balance were performed in the setting of thrice‐weekly “conventional” dialysis. While the effect of the increase in dialysis frequency and/or duration on uraemic bone disease has been extensively described, nonconventional schedules, such as incremental or short daily dialysis, have been less studied by intradialysis profiles . Furthermore, the new generation of portable dialysis machines, with low‐flow dialysate, presents a different mass transfer profile, which has not yet been completely clarified …”
Section: Introductionmentioning
confidence: 99%
“…There has been increased interest in more frequent and intensive dialysis therapies as a means of improving these outcomes in the hope that this will reduce mortality among dialysis patients. Daily hemodialysis (DHD) has been associated with improved survival, nutrition, and mineral metabolism 10–20 . Improvements in quality of life have also been associated with DHD 21–25 .…”
Section: Introductionmentioning
confidence: 99%
“…Daily hemodialysis (DHD) has been associated with improved survival, nutrition, and mineral metabolism. [10][11][12][13][14][15][16][17][18][19][20] Improvements in quality of life have also been associated with DHD. [21][22][23][24][25] Cardiovascular benefits include improved blood pressure control, higher hemoglobin levels, and regression of left ventricular hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Daily hemodialysis has been associated with favorable surrogate markers of improved survival among hemodialysis patients. These outcomes include improvements in left ventricular mass index, chronic inflammation, nutritional markers and mineral metabolism markers . There is currently no study that directly addresses the impact of daily dialysis on vascular access outcomes over long‐term follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…These outcomes include improvements in left ventricular mass index, chronic inflammation, nutritional markers and mineral metabolism markers. [1][2][3][4][5] There is currently no study that directly addresses the impact of daily dialysis on vascular access outcomes over longterm follow-up. Previous observational and uncontrolled studies of daily hemodialysis have shown mixed results in regards to vascular access outcomes with the majority showing no difference in access outcomes [5][6][7][8][9] and some showing a trend toward improved access outcomes.…”
Section: Introductionmentioning
confidence: 99%